THE DISTINCTION OF LANGUAGE CLASS BETWEEN HIGH AND LOW AFFECTIVE FILTERS - Ramdaniyah, Nurul Annisa; Sumarna, Yuniarsih (IJLECR (International Journal of Language Education and Cultural Review), 2019)
ABSTRACT Learning language is a process of acquiring language. The successful of learning is influenced by whole aspects of learning such as learning environment. Krashen (1986) suggested, the teacher should create the learning environments as safe and comfort as possible, so all of the input which is given by the teacher can be accept well by the students. Moreover, there is a filter between teacher and student that could become a block input in acquiring language called affective filter. How high or how low the affective filter, it could influence to the learning process. In this study, the researcher tried to find the distinctions between classes with high and low affective filter. This study was conducted in Suryakancana University. The sample was an English class of English Education Study Program. The data gained by observed the class and giving the open-ended questionnaires. The result of the study shows that the class with high affective filter is uncomfortable for the student, and in contrast, the class with low affective filter make students feel comfortable in learning process. Keywords: learning, English class, High Affective filter, Low affective filter